Fibrinolysis in Obstetrical Coagulopathy - Zilliacus, H (Thrombosis and Haemostasis, 1961)
In the introduction it is stressed that in cases with normal blood coagulation and even in cases with a limited decrease of some of the coagulation factors, the contraction of the uterus after the passage of the placenta closes the vessel endings, thereby providing the conditions necessary for haemostasis through the clotting of the blood. In contrast to this, fibrinolytic uterine bleeding is a condition in which the clotting factor and clot are consumed despite adequate postpartum contraction of the uterus.The literature on obstetrical coagulopathies is briefly summarized.The incongruence in the clotting power of blood samples drawn simultaneously from a cubital vein and from the uterus in cases of severe uterine haemorrhage is pointed out.With the aid of a plasma-dilution technique (Schneider) for the estimation of fibrinogen and fibrinolysis it was shown that in 6 out of 8 investigated cases of premature separation of the placenta, in 4 out of 5 observed cases of longstanding intrauterine foetal death and in 2 cases of pitocin drip induced labor considerable fibrinolytic activity was present in the blood from the uterus, whereas only slight activity if any, could be observed in blood samples drawn simultaneously from a cubital vein. These observations are found to be in conformity with the finding of considerable amounts of fibrinolytic activators in myométrial, placental and decidual tissue reported by other authors.Figures for obstetrical cases (19,808 deliveries) and uterine haemorrhage during the 5-year period 1955—1959 at the 1st Department of Obstetrics and Gynaecology, University Central Hospital, Helsinki, Finland, are presented. The main principles of obstetrical management at this hospital are outlined, with special reference to uterine coagulopathic haemorrhage.